Application of HEC-HMS model and satellite precipitation products to restore runoff in Laigiang river basin in Vietnam - Ngo Anh Tu; Nguyen Huu Xuan; Nguyen Thi Tuong Vi; Phan Thai Le (Faculty of Geography, Universitas Gadjah Mada, 2022)
The Laigiang river basin in the South Central Coast of Vietnam plays an important role in the socio-economic development of Binhdinh Province. In recent decades, the region has experienced commonly flooding in vast areas. This research aims to simulate event-based rainfall-runoff modelling, a historical flood event in December 2016, by applying the HEC-HMS model and rainfall data from CHIRPS. The CHIRPS data is an acceptable potential data input of the hydrology model. These have been confirmed through reliable validation indexes: The peak flood flow rate of 2,542.6 m3/s corresponds to the flood frequency of 5%; NSE with the value at 0.95; R2 coefficient reached 0.87; PBIAS being around 0.45, and PFC being at 0.89. It shows better performance in the rainy season than in the dry season. Inclusive, the CHIRPS rainfall data set and the HEC model could be used for some operational purposes in weather forecasting, especially for flood warnings in river basins in the South Central Coast, Vietnam.